The enhanced fault-tolerance mechanism of AODV routing protocol for Wireless Sensor Network - Che-Aron, Zamree; Al-Khateeb, Wajdi Fawzi Mohammed; Anwar, Farhat (IJCSNS, 2010)
As more and more real Wireless Sensor Network’s (WSN) applications are tested and deployed over the last decade, the research community of WSN realizes that several issues need to be revisited from practical angles, such as reliability and availability. Basically, wireless sensor networks suffer from resource limitations, high failure rates and faults caused by the defective nature of wireless communication and the wireless sensor characteristics. This can lead to situations, where nodes are often interrupted during data transmission and blind spots occur in the network by isolating some of the devices. In this paper, we address the reliability issue by designing and developing an enhanced fault-tolerance mechanism of Ad hoc On-Demand Distance Vector (AODV) routing protocol for WSN called the ENhanced FAult-Tolerant AODV (ENFAT-AODV) routing protocol. The proposed ENFAT-AODV routing protocol improves the reliability and robustness of the network by creating a backup path for every node on a main path of data delivery. When the node gets failure to transmit a data packet through the main path, it immediately utilizes its backup route to become a new main path for the transmission of next coming data packets without any interruption. This protocol reduces the number of dropped data packets and maintains the continuity of data packet transmission in presence of network faults. The simulation results prove that the proposed ENFAT-AODV routing protocol enhances the original AODV in term of the reliability, availability and fault-tolerant ability of the network.